Role of IKKε in the Metabolic Diseases: Physiology, Pathophysiology, and Pharmacology - Xiao, Qing-Ao; He, Qian; Li, Lun; Song, Yinhong; Chen, Yue-ran; Zeng, Jun; Xia, Xuan (Frontiers in Pharmacology, 2022)
IKKε (inhibitor of nuclear factor kappa-B kinase ε) is a member of non-canonical NF-κB pathway. It participates in inflammatory response and innate immunity against bacteria. For recent decades, IKKε has been closely associated with metabolic regulation. Inhibition of IKKε pathway can improve fat deposition in liver, reduce subcutaneous fat inflammation and liver gluconeogenesis in obesity. IKKε is expected to be a new therapeutic target for metabolic diseases including non-alcoholic fatty liver disease, diabetes and obesity. Herein, we summarize the structural characterization, physiological function and pathological role of IKKε in metabolic diseases and small molecule inhibitors of IKKε.